The Baby-sitters club. 5, Dawn and the impossible three - Galligan, Gale.; Martin, Ann M., 1955- (New York, NY : Graphix, an imprint of Scholastic, 2017)
As a new member of the Baby-sitters Club, Dawn tries to win the acceptance of the club's president by tackling a tough babysitting job.
"Based on the novel by Ann M. Martin"--Front cover.
Based on: Dawn and the impossible three / Ann M. Martin.
Kirkus Review
School Library Journal
Kirkus Review, July 2017
School Library Journal, July 2017
Keywords: Babysitters Club (Imaginary organization) -- Comic books, strips, etc. -- Juvenile fiction; Babysitters -- Comic books, strips, etc. -- Juvenile fiction; Clubs -- Comic books, strips, etc. -- Juvenile fiction; Friendship -- Comic books, strips, etc. -- Juvenile fiction; Babysitters Club (Imaginary organization) -- Fiction; Babysitters -- Fiction; Clubs -- Fiction; Friendship -- Fiction; Babysitters Club (Imaginary organization) -- Comic books, strips, etc. -- Fiction; Babysitters -- Comic books, strips, etc. -- Fiction; Clubs -- Comic books, strips, etc. -- Fiction; Friendship -- Comic books, strips, etc. -- Fiction; Graphic novels